Sub-cellular location of FtsH proteases in the cyanobacterium Synechocystis sp PCC 6803 suggests localised PSII repair zones in the thylakoid membranes - Sacharz,J; Bryan,SJ; Yu,J; Burroughs,NJ; Spence,EM; Nixon,PJ; Mullineaux,CW (Molecular Microbiology, 2015)
In cyanobacteria and chloroplasts, exposure to HL damages the photosynthetic apparatus, especially the D1 subunit of Photosystem II. To avoid chronic photoinhibition, a PSII repair cycle operates to replace damaged PSII subunits with newly synthesised versions. To determine the sub-cellular location of this process, we examined the localisation of FtsH metalloproteases, some of which are directly involved in degrading damaged D1. We generated transformants of the cyanobacterium Synechocystis sp. PCC6803 expressing GFP-tagged versions of its four FtsH proteases. The ftsH2–gfp strain was functional for PSII repair under our conditions. Confocal microscopy shows that FtsH1 is mainly in the cytoplasmic membrane, while the remaining FtsH proteins are in patches either in the thylakoid or at the interface between the thylakoid and cytoplasmic membranes. HL exposure which increases the activity of the Photosystem II repair cycle led to no detectable changes in FtsH distribution, with the FtsH2 protease involved in D1 degradation retaining its patchy distribution in the thylakoid membrane. We discuss the possibility that the FtsH2–GFP patches represent Photosystem II ‘repair zones’ within the thylakoid membranes, and the possible advantages of such functionally specialised membrane zones. Anti-GFP affinity pull-downs provide the first indication of the composition of the putative repair zones.